Attenuation of cartilage pathogenesis in post‐traumatic osteoarthritis (PTOA) in mice by blocking the stromal derived factor 1 receptor (CXCR4) with the specific inhibitor, AMD3100. Issue 7 (24th April 2015) - Thomas, Nathan P.; Li, Pengcui; Fleming, Braden C.; Chen, Qian; Wei, Xiaochun; Xiao‐Hua, Pan; Li, Gang; Wei, Lei
ABSTRACT SDF‐1 was found to infiltrate cartilage, decrease proteoglycan content, and increase MMP‐13 activity after joint trauma. In this study, we tested the hypothesis that interference of the SDF‐1/CXCR4 signaling pathway via AMD3100 can attenuate pathogenesis in a mouse model of PTOA. We also tested the predictive and confirmatory power of fluorescence molecular tomography (FMT) for cartilage assessment. AMD3100 was continuously delivered via mini‐osmotic pumps. The extent of cartilage damage after AMD3100 or PBS treatment was assessed by histological analysis 2 months after PTOA was induced by surgical destabilization of the medial meniscus (DMM). Biochemical markers of PTOA were assessed via immunohistochemistry and in vivo fluorescence molecular tomography (FMT). Regression analysis was used to validate the predictive power of FMT measurements. Safranin‐O staining revealed significant PTOA damage in the DMM/PBS mice, while the DMM/AMD3100 treated mice showed a significantly reduced response with minimal pathology. Immunohistochemistry showed that AMD3100 treatment markedly reduced typical PTOA marker expression in chondrocytes. FMT measurements showed decreased cathepsins and MMP activity in knee joints after treatment. The results demonstrate that AMD3100 treatment attenuates PTOA. AMD3100 may provide a viable and expedient option for PTOA therapy given the drug's FDA approval and well‐known safety profile. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1071–1078, 2015.